1988
DOI: 10.1042/bj2490319
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing and overexpression of the Escherichia coli aroE gene encoding shikimate dehydrogenase

Abstract: The Escherichia coli aroE gene encoding shikimate dehydrogenase was sequenced. The deduced amino acid sequence was confirmed by N-terminal amino acid sequencing and amino acid analysis of the overproduced protein. The complete polypeptide chain has 272 amino acid residues and has a calculated Mr of 29,380. E. coli shikimate dehydrogenase is homologous to the shikimate dehydrogenase domain of the fungal arom multifunctional enzymes and to the catabolic quinate dehydrogenase of Neurospora crassa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 50 publications
1
39
0
Order By: Relevance
“…1). The NADP-dependent shikimate-specific enzyme is involved in the biosynthetic role (1). On the other hand, it is likely that the enzyme involved in the catabolic role acts on both quinate and shikimate as substrates and prefers NAD as a coenzyme in fungi and gram-positive bacteria, although genetic characterization of the bacterial enzymes is obscure (3,12,14).…”
Section: Vol 75 2009mentioning
confidence: 99%
See 1 more Smart Citation
“…1). The NADP-dependent shikimate-specific enzyme is involved in the biosynthetic role (1). On the other hand, it is likely that the enzyme involved in the catabolic role acts on both quinate and shikimate as substrates and prefers NAD as a coenzyme in fungi and gram-positive bacteria, although genetic characterization of the bacterial enzymes is obscure (3,12,14).…”
Section: Vol 75 2009mentioning
confidence: 99%
“…Unrooted phylogenetic tree showing relationships among bacterial shikimate dehydrogenase family proteins and the homologues in C. glutamicum. The proteins analyzed were E. coli AroE and YdiB (AroE-Ec and YdiB-Ec) (1,24), H. influenzae AroE and SdhL (AroE-Hi and SdhL-Hi) (36,47), M. tuberculosis shikimate dehydrogenase (SDH-Mt) (10), Amycolatopsis mediterranei RifI (RifI-Am) (48), and C. glutamicum QsuD, CgR_1216, and CgR_1677, encoded by qsuD, cgR_1216, and cgR_1677, respectively. The amino acid sequences were aligned using the CLUSTAL W program (40), and the tree was constructed using the neighbor-joining method (31).…”
Section: Vol 75 2009mentioning
confidence: 99%
“…nidufans (Anarom), S. cerevisiae (Scarom), and P. carinii (Pcarom) AROM enzymes and also a composite of the E. cofi monofunctional enzymes which have been arranged in the following order: DHQ synthase (residues 1-363) ; EPSP synthase (364-789) (Duncan et af., 1984); shikimate kinase (790-963) (Millar e f al., 1986); DHQ dehydratase (966121 5 ) and shikimate dehydrogenase (1216-1487) (Anton & Coggins, 1988). The sequence of DHQ dehydratase has been amended from that originally published (Duncan er af., 1986) following the corrections specified by Chaudhuri et af.…”
Section: Fig 3 Volfowing Three Pages)mentioning
confidence: 99%
“…Recently it has been shown, by site-directed mutagenesis of the A. nidulans AROM locus, that some ofthe arom polypeptide (including the bDHQase domain) can fold and function in Escherichia coli as monofunctional enzymes [24]. In addition, a study of protein sequences deduced from DNA sequence data has shown that the quinate dehydrogenase enzyme of the quinic acid utilization pathway and the shikimate dehydrogenase enzyme of the shikimate pathway have evolved from a common ancestral sequence [5,19]. Conversely, the comparison of bDHQase and cDHQase enzyme sequences has led to the proposal that the two enzymes arose by convergent evolution [23,25].…”
Section: Introductionmentioning
confidence: 99%
“…Lamb et al [12] have shown that the common metabolites 3-dehydroquinate and dehydroshikimate leak from the arom protein at a rate comparable with the flux of metabolites through the shikimate pathway and can be utilized by the enzymes of both pathways. A similar fused polypeptide is also present in Neurospora crassa [13][14][15] and Saccharomyces cerevisiae [16] but, in prokaryotes, steps two to six in the shikimate pathway are catalysed by distinct monofunctional enzymes [17][18][19][20][21] that are constitutively expressed and are not required to aggregate for activity. Evidence from DNA sequence analysis has strongly suggested that the complex AROM locus arose by multiple gene fusions to generate the pentafunctional arom polypeptide [22,23].…”
Section: Introductionmentioning
confidence: 99%